Impact of the Legend Shiyali Ramamrita Ranganathan's Cited Research Articles through Google Scholar - Kumar, K. (Journal of Information and Knowledge, 2016)
This paper quantifies and analyzes the impact of research publications of Shiyali Ramamrita Ranganathan. The data for the study obtained using a web browser plug-in called Scholarometer through the Google Scholar, a search engine for scholarly communications. The study found 60 unique documents of S. R. Ranganathan. The paper analyzes the citations received by those research works through documents cited S. R. Ranganathan's work, citation count by document type, authorship pattern and discipline wise distribution of publications. This article also examines citation database using various research impact factors such as h-index, hm-index, hf-index and g-index. In addition, link analysis performed to provide interactive visualization of S. R. Ranganathan network displaying number of citation per author.